2009
DOI: 10.1007/s00167-009-0890-1
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical evaluation of a single-row versus double-row repair for complete subscapularis tears

Abstract: The purpose of the study was to compare a single-row repair and a double-row repair technique for the specific characteristics of a complete subscapularis lesion. Ten pairs of human cadaveric shoulder human shoulder specimens were tested for stiffness and ultimate tensile strength of the intact tendons in a load to failure protocol. After a complete subscapularis tear was provoked, the specimens were assigned to two treatment groups: single-row repair (1) and a double-row repair using a "suture bridge" techniq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
40
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 39 publications
3
40
0
Order By: Relevance
“…Moreover, a load of 180 Newton represents approximately 20 % of the ultimate failure load of the intact tendon [42], which might also be a viable load in the early post-operative period. Finally, ultimate tensile strength was tested.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, a load of 180 Newton represents approximately 20 % of the ultimate failure load of the intact tendon [42], which might also be a viable load in the early post-operative period. Finally, ultimate tensile strength was tested.…”
Section: Methodsmentioning
confidence: 99%
“…Biomechanical tests have shown that the TOE repair technique is superior to the unlinked double-row and single-row methods for the repair of the supraspinatus 30,32 and subscapularis. 36 However, to our knowledge, no study comparing the outcomes of arthroscopic TOE and single-row repairs of anterosuperior RCTs has yet been published. Thus, the purpose of this study was to compare the outcomes of TOE and single-row repairs in patients undergoing arthroscopic repair of anterosuperior RCTs.…”
mentioning
confidence: 98%
“…1 Pictures showing the different arthroscopic portals used for subscapularis repair using the suture-bridge technique (a anterior, b lateral, c posterior, d low anteromedial, e low anterolateral) Fig. 2 Arthroscopic view of high-speed burr brought into the subacromial space through the anterolateral portal to decorticate the lesser tuberosity subscapularis tendon [14], the double-row technique restored higher ultimate load and stiffness compared to that of the single-row technique. Therefore, from a biomechanical point of view, double-row fixation is more recommendable than single-row repair.…”
Section: Discussionmentioning
confidence: 99%
“…Although single-row repair for subscapularis tendon tears showed good results regarding shoulder function and repaired cuff integrity, concerns still remain for retear rate, as reported 35% for arthroscopic fixation of combined anterosuperior tears (subscapularis and supraspinatus tendon tears) [6,8]. Recent biomechanical study revealed that double-row technique restored significant higher ultimate load and stiffness compared to those of single-row technique [14]. The suturebridge technique has been adapted for arthroscopic subscapularis repair to attain the ideal cuff integrity and footprint restoration.…”
Section: Introductionmentioning
confidence: 99%